Physical characteristics, mineral analysis and antioxidant properties of some apricot varieties grown in North India - S.M. Wani; F.A. Masoodi; Touseef Ahmed Wani; Mukhtar Ahmad; Adil Gani; S.A. Ganai (Cogent Food & Agriculture, 2015)
Eleven apricot varieties (Chinese, Rival, Tilton, Cuminis Haley, Harcot, Margulam, Narmu, Khante, Halman, Badam Chuli, and Cuban) were studied for their mineral analysis, physical characteristics, and antioxidant properties. The physical characteristics varied significantly (p ≤ 0.05) among the apricot varieties. Cuban and Harcot showed a comparatively larger fruit size. However, Cuminis Haley and Harcot showed the highest edible bulk. Nine minerals (Zn, Ca, Cu, Fe, Mg, Na, Mn, P, and K) were analyzed and were found to vary significantly (p ≤ 0.05) among the apricot varieties. Mn, Cu, and Zn elements were present in micro amounts, while K, Mg, Ca, P, and Fe levels were present in macro amounts. Halman and Margulam showed significantly (p ≤ 0.05) higher amount of the minerals. All the varieties showed lower amounts of Cu as compared to the recommended daily intake, ranging from 0–0.82 ppm. All the varieties proved to be rich sources of polyphenols, with significant (p ≤ 0.05) varietal difference. Khante and Halman showed the significantly (p ≤ 0.05) highest methanolic 1,1-diphenyl-2-picrylhydrazyl (DPPH•) radical scavenging activity.